Exploring Students' Level of Conceptual Understanding on Periodicity - Necor, Dexter (JPAIR Multidisciplinary Research, 2018)
Nowadays, many science studies motivated on addressing the conceptual understanding particularly in chemistry that soon may affect students' academic performance. This study covered the level of conceptual understanding on the trends of the periodic table of elements and the type of conceptual change before and after the exposure of interventions. The qualitative and quantitative research method were used in the study. Respondents were Grade 10 high school students. Frequency, percentage, and t-test were the statistical tools applied to answer specific questions. Results revealed that most students have an ambiguous conceptual understanding.  The trends in ionization energy (I.E.) noted the highest misconception statements followed by the trends in atomic radius (A.R.).  The trends in electron affinity (E.A.); formation of cation and anion (I.R.); and electronegativity (E.) were also least understood by the students. After interventions, there is a marked increase in students who progressed from misconception (MU) to full understanding (FU). This is prevalent on the trends in atomic radius, followed by the trends in electron affinity and the formation of ions.  The use of varied activities such as visualizing and multimedia tools; small-group discussions; and concept mapping have a vital positive outcome in their progression. Ergo, science teachers should vary their teaching strategies to address and correct students' conceptual obstacles in learning chemistry concepts.
Keywords: Chemical education; conceptual understanding; descriptive; remedial activities; Philippines